Relationship Between The Level Of Knowledge About Sexually Transmitted Disease (STDs) And Personal Hygiene Behavior Of External Genitalia Organs In Female Teenagers - Ariani, Novida; Asmika, Asmika; Hanesty, Avila (Jurnal EduHealth, 2024)
Background: Sexually Transmitted Disease (STDs) are a health problem that is still quite critical and receives attention until now. This disease often affected by teenagers aged 15-24 years, especially female teenagers. One of the factors causing the emergence of sexually transmitted disease in female teenagers is the vulnerability of external genitalia organs to infection. If this is followed by poor personal hygiene behavior and is not treated immediately, it can cause infertility. Purpose: To find out the relationship between the level of knowledge about sexually transmitted disease and personal hygiene behavior of external reproductive organs in female teenagers at SMA Brawijaya Smart School Malang. Methodes: The research design used analytical observational by cross sectional approach. A total of 84 female students were sampled according to the inclusion and exclusion criteria. Data was obtained through instruments research in the form of questionnaires filled in by respondents. Then, data is presented in the form of frequency distribution table and processed using chi-square test method. Result: The results showed that there was a significant relationship between the level of knowledge about sexually transmitted disease and personal hygiene behavior of external genitalia organs in female teenagers. Conclusion: Based on results of research, there was a relationship between the level of knowledge about sexually transmitted disease and personal hygiene behavior of external genitalia organs in female teenagers at SMA Brawijaya Smart School Malang. Female Teenagers are advised to maintain reproductive health with increase the knowledge from trusted sources so that understanding does not become wrong.